Social Capital and Conflict in the Post-Suharto Regime in Indonesia - Hesda, Andar Ristabet; Nasrudin, Rus'an (Economics and Finance in Indonesia, 2023)
This study explores the relationship between social capital and conflict in the post Suharto regime in Indonesia. We employed a combination of cross-section datasets from the Social and Cultural Module of the 2009 National Socio- Economic Survey (SUSENAS) and the media-based conflict data from National Violence Monitoring System (NVMS) of 2010–2014 in Indonesia. Using Binomial Negative Regression, our empirical analysis shows that the past social capital stocks negatively correlate with future conflict intensity. This pattern applies to most conflict types. This result indicates that the social capital stock in 2009 is more likely to be the starting point determining the conflict vulnerability in the subsequent period. Furthermore, the evaluation of the components of social capital reveals that the most crucial type of social capital is trust in neighbors, the government, and local officials. The district with high trust is less prone to conflict.